Pengembangan Modul dan Trainer Pengemas Barang Untuk Pembelajaran FBD di Jurusan Teknik Elektro Universitas Negeri Malang - Jefri, Achmad; Sendari , Siti (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2020)
The objectives of this research are (1) to design development of instructional media in form of modules and product packaging trainers for Industrial Automation Workshop courses in Department of Electrical Engineering, Faculty of Engineering, State University of Malang, (2) developing product packaging trainers that have been made it can be used for a variety of systems (microcontrollers, smart relays, and PLCs), (3) developing product packaging trainer practicum module based on smart relay for learning FBD (Function Block Diagram) programming in Industrial Automation Workshop course in Department of Electrical Engineering, State University of Malang and, (4) testing feasibility of module and trainer of goods packaging that have been developed for learning courses in Industrial Automation Workshop in the Department of Electrical Engineering, Faculty of Engineering, State University of Malang. This study adopting a development tailored model to needs of module development but still refers to existing development models. Development model in this research uses development model from Sugiyono tailored to needs. Based on results of validation and feasibility testing of practicum modules by experts 1, experts 2, product trials and usage trials can be concluded that practicum modules and product packaging trainers are very suitable used in learning